BEFORE, DURING AND AFTER COVID-19: STUDY ON TOURSIM & HOSPITALITY BUSINESS IN INDIA - Mukesh Mukesh; Prof. Mahabir Narwal (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Tourism helps in creating job possibilities either directly or indirectly and also play a part in the contribution of foreign exchange of the country. Tourism are of different type and for analyze purpose, one should understand the difference between all forms of tourism like discussed in this study. As a tour, one can travel away from permanent location to the place which is not in the same location. To travel from one place to other were restricted due to COVID-19 and it places a big impact on tourism and hospitality business in India and in world. During COVID-19, leisure and business tourists revoked their trips which were planned and scheduled due to rose in positive cases and government guidelines. Tourism and hospitality business faced a huge loss due to lockdown as well as it affected employment of people. Tourism industry is a good source of revenue generation and backbone of economy in many countries. The aim of this study is to see before, during and after COVID-19 impact on hospitality and tourism business in India